Gastroprotective Effects of the Combination of Chromolaena odorata L. and Pachyrhizus erosus L. Extracts on Rats with Gastric Ulcer Model - Reza Pertiwi; Reza Rahmawati; Aanisah Hanuun; Noval Kurnia Wati; Tesa Pebiani; Ridho Kurnia; Wafa Syahidah; Risky Hadi Wibowo; Doni Notriawan (Sanata Dharma University, 2023)
Gastroprotective effects are caused by compounds that can protect the gastric mucosa. Gastroprotective activity provided by plants is due to the presence of a group of secondary metabolite compounds found in the plants. The types of secondary metabolite compounds are flavonoids, tannins, alkaloids and saponins. Chromolaena odorata L. contains tannins, phenols, flavonoids, saponins and steroids, while Pachyrhizus erosus L. is known to contain flavonoids and saponins. This study aimed to determine the gasprotective activity of the combination of Chromolaena odorata L. and Pachyrhizus erosus L. extracts in ethanol-induced rats by observing the parameters of the number of peptic ulcers, protection ratio, and images of gastric histopathology. The research method was to make a combination of Chromolaena odorata L. and Pachyrhizus erosus L. extracts which were given to six treatment groups: normal group without treatment; negative control group; positive control group given sucralfate; and three groups given a combination treatment of Chromolaena odorata L. and Pachyrhizus erosus L. extract with a dose of 100, 200, and 400 mg/kgBW. Treatment was done by oral administration for 14 days. On Day 14, after one hour of treatment, 96% ethanol induction was given orally at a dose of 2 ml/200 gBW except for the normal group. The ulcer index produced by negative control, positive control, the treatment with doses of 100, 200, and 400 were 4.18; 2.98; 2.49; 1.64; and 0.78, respectively. The combination of Chromolaena odorata L. and Pachyrhizus erosus L. extracts can prevent gastric damage in rats caused by ethanol induction.